2020
DOI: 10.1002/joc.6603
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the impact of soil moisture on spring surface air temperature over the low‐latitude highlands of China

Abstract: The low-latitude highlands (LLH) of China are situated in the subtropical southwest China. The spring climatic characteristics of the LLH were previously regarded as being governed by remote sea surface temperature forcing and large-scale atmospheric circulations. Recent studies qualitatively demonstrated that the LLH is a relatively strong soil moisture (SM)-surface air temperature (SAT) coupling region in China during spring. In this study, the quantitative spring SM-SAT coupling (mean of March and April bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 66 publications
(99 reference statements)
0
5
0
Order By: Relevance
“…In previous studies, changes in soil moisture were investigated in different areas and habitats [61][62][63][64]. Discerning changes in soil moisture is a very complex process, as it is not only affected by the length of precipitation events [24], but also by precipitation intensity [65], vegetation type, soil texture, and other factors.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, changes in soil moisture were investigated in different areas and habitats [61][62][63][64]. Discerning changes in soil moisture is a very complex process, as it is not only affected by the length of precipitation events [24], but also by precipitation intensity [65], vegetation type, soil texture, and other factors.…”
Section: Discussionmentioning
confidence: 99%
“…Soil moisture can impact surface energy partitioning, affecting surface air temperature through land‒atmosphere coupling (Dirmeyer & Halder, 2017; Wang et al., 2011; Zeng et al., 2019). Surface flux changes can be measured by the Bowen ratio, defined as the ratio of sensible heat flux to latent heat flux (Bowen, 1926; Qin et al., 2018; Zhao et al., 2020). In general, the larger the Bowen ratio is, the more surface net radiation is allocated to sensible heat flux, contributing to an increase in surface air temperature.…”
Section: Methodsmentioning
confidence: 99%
“…While in the subtropical southwest of China, soil moisture contributed 10%-50% of the total air temperature variance (J. Zhao et al, 2020). Over the monsoon-dominated region of India, the long-term decrease of soil moisture increased the incidence of temperature extremes (Ganeshi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Research has indicated that soil moisture feedback over North China contributes 6% of the total air temperature variation from 1961 to 2012 and reaches 36% after the regional warming from 1994 to 2012 (B. Xu et al, 2019). While in the subtropical southwest of China, soil moisture contributed 10%–50% of the total air temperature variance (J. Zhao et al, 2020). Over the monsoon‐dominated region of India, the long‐term decrease of soil moisture increased the incidence of temperature extremes (Ganeshi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%